Procedimiento Administrativo del Personal en el Departamento de Compras Públicas del GAD del Cantón Montalvo - Rosario Stefania Solórzano Vistìn, Rosario Stefania (2017)
The Municipality of Montalvo has the objective of Legislation, Normativity and Control, Execution and Administration, Citizen Participation and Social Control. At present the Msc. Elifonso Clemente Cortés Martínez is the mayor of the canton Montalvo, possessed on May 20, 2014